Determination of Soil and Water Contamination aroundan Industrialized Town, Kazanli, Mersin, Turkey - KEMAL SANGUN, MUSTAFA; GOKSEL OZDILEK, HASAN (Asian Journal of Chemistry, 2010)
In this study, concentrations of selected metals, namely chromium and nickel, in groundwater and soil were investigated. It was found that extensive chromium and nickel levels in soil. that had been used for building materials and this could probably impair public and environmental health, such as in sea turtles, in the area. Toxicological risk assessment from water quality criteria indicated that aquatic toxicity from both acute and chronic nickel and chromium does not exceed estimated ecotoxicology levels.